How do Rausyan Fikr Manage a Violence? - Watini Watini (Nizham Jurnal Studi Keislaman, 2017)
Muslims is divided into two groups, Sunni and Shi’ite. The majority of muslim in Southeast Asia is Sunni. Shi’ite exist in Southeast Asia including Indonesia. Shi’ite was in Southeast Asia since long time ago approximately in 7th century. In Yogyakarta, Indonesia there are foundation that examine Shi’ism. The examination is about phylosophy. It is established in 1990s. Twenty two years after establishment there is no violence or controversion but since 2013 the problem emerged. Rausyan Fikr have own resolution to solve the problem.